The physical education curriculum and life skills: Processes and intervention strategies - Fernando Santos; Rui Neves; Paulo Pereira; António Cardoso (Desafio Singular, 2020)
Positive youth development has been used as an approach that may help physical education teachers focus on youth's assets and foster life skills. This article aims to offer reflections that may guide curricular changes across educational contexts and help identify priorities derived from existent research in the field of positive youth development through physical education. There is the need to conduct a reflection about the perspective towards physical education present in the formal curriculum, as well as on the possible consequences of this perspective on the hidden curriculum and physical education teachers' practices. The formal curriculum may be strategically used to make positive youth development objectives, outcomes, and strategies explicit through the existent research and communities' needs to attain better outcomes.